Effectiveness of primary-contact physiotherapy in managing musculoskeletal conditions in emergency departments: protocol for the RESHAP-ED randomised controlled trial - Rachelle Buchbinder; Andrew Lawson; Bethan Richards; Kirsten Howard; Vasi Naganathan; Michael Dinh; Kirsten McCaffery; Thomas Lung; Laurent Billot; Ian Harris; Gustavo C Machado; James Edwards; et al. (BMJ Open)
Introduction Patients with musculoskeletal conditions often seek care in an emergency department (ED). The problem is that the time required to manage these patients places an additional pressure on ED physician and nursing staff, who are primarily trained and resourced to manage high-acuity patients. Primary-contact physiotherapists could play a greater role in supporting ED physician and nursing staff in the management of patients presenting to the ED with musculoskeletal conditions.Methods and analysis The RESHAP-ED trial is a multicentre, pragmatic, open-label, two-arm, parallel randomised controlled trial with nested process and economic evaluations. The trial will investigate whether a primary-contact physiotherapy pathway compared with usual care (primary-contact by physician and/or nursing staff pathway) reduces time spent in ED. Patients with simple musculoskeletal conditions will be recruited from EDs in New South Wales, Australia. The primary outcome is ED length of stay (LOS). Secondary outcomes will include acceptability, feasibility and cost-effectiveness of primary-contact physiotherapy, and explore patients’ and clinicians’ experience. To detect a 30 min between-group difference in ED LOS, 1370 patients will be required. Analyses of the primary and secondary outcomes will be conducted following the intention-to-treat principle. The adjusted mean difference in ED LOS and 95% CI will be calculated using linear regression adjusted for hospital using a random effect model.Ethics and dissemination The study received ethical approval from the Sydney Local Health District (RPAH zone) Human Research Ethics Committee (X23-0143). Findings from this study will be disseminated through publication in peer-reviewed journals and conference presentations.Trial registration number Australia New Zealand Clinical Trials Registry: ACTRN 12623000782639; Universal Trial Number (UTN): U1111-1292-2883.